2023
DOI: 10.1590/1984-0462/2023/41/2022123
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a standardized handoff system (I-PASS) in a tertiary care pediatric hospital

Abstract: Objective: The handoff is the act of transferring information and responsibility among healthcare providers, and it is critical for the patient safety and the quality of service. The aim of this study was to evaluate the implementation of a standardized medical handoff system [I-PASS (Illness severity, Patient summary, Action list, Situation awareness and contingency planning, Synthesis by receiver)] and assess the effect on the amount and quality of the information transmitted during medical handoffs in a ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study found that caregivers faced several challenges in accessing healthcare services and experienced high levels of stress and social isolation. Soares et al (2023) [12], in their study, focused on the implementation of a standardized handoff system in a tertiary care pediatric hospital in Brazil. The study showed that the implementation of the I-PASS system (a standardized handoff system) improved the quality of communication during handoffs and reduced medical errors.…”
Section: Editorialmentioning
confidence: 99%
“…The study found that caregivers faced several challenges in accessing healthcare services and experienced high levels of stress and social isolation. Soares et al (2023) [12], in their study, focused on the implementation of a standardized handoff system in a tertiary care pediatric hospital in Brazil. The study showed that the implementation of the I-PASS system (a standardized handoff system) improved the quality of communication during handoffs and reduced medical errors.…”
Section: Editorialmentioning
confidence: 99%